Teknik Relaksasi Nafas Dalam dengan Adaptasi Nyeri Persalinan Kala I Fase Aktif - Surinati I Dewa Ayu Ketut (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2013)
This study aimed to analyze the relationship of relaxation techniques with the adaptation of breathing in pain an active phase inpartu. This research is observational analytic approach used method is cross sectional technique. The model approruch used is the subjec of of cross sectional. Sampling technique used in this research was consekutif sampling by using sample counted 22 responden. Analysis of the data by Spearmen Rank Correlation test . The results of this study indicate that there is a significant relationship between the relationships breathing relaxation techniques with the adaptation of labor pain in women in the active phase inpartu, p=0,000 and r = 0,913